Rozwiąrz równanie.
x^4-9x^2-10=0
x^4-8x^2-9=0


Odpowiedź :

[tex]a)\\\\x^4-9x^2-10=0\\t=x^2\\t^2-9t-10=0\\\\\Delta=(-9)^2-4*1*(-10)=81+40=121\\\sqrt{\Delta}=11\\t_1=\frac{9-11}2=\frac{-2}2=-1\\t_2=\frac{9+11}2=\frac{20}2=10\\\\x=\sqrt{t}\\x_1=\sqrt{-1} - \text{liczba urojona, to nie rozwiazanie}\\\underline{x_2=\sqrt{10}}\\\underline{x_3=-\sqrt{10}}[/tex]

[tex]b)\\\\x^4-8x^2-9=0\\t=x^2\\x=\sqrt{t}\\\\t^2-8t-9=0\\\Delta=(-8)^2-4*1*(-9)=64+36=100\\\sqrt{\Delta}=10\\\\t_1=\frac{8-10}2=\frac{-2}2=-1\\t_2=\frac{8+10}2=\frac{18}2=9\\\\x_1=\sqrt{-1} - \text{liczba urojona}\\x_2=-\sqrt{-1} - \text{liczba urojona}\\\\\underline{x_3=\sqrt{9}=3}\\\underline{x_4=-\sqrt9=-3}[/tex]

Rozwiazania sa podkreslone